Mecanismo de acción del factor estimulante de colonias de granulocitos (G-CSF) en células trofoblásticas humanas - Furmento, Verónica Alejandra (2015)
In order to investigate the functional role of G-CSF:G-CSFR interaction in placental tissues we employed a trophoblastic cell line (Swan 71) derived from first trimester human cytotrophoblast explants. After detecting the presence of G-CSF receptors in these cells, we found that the cytokine didn?t behave as a proliferative stimulus neither promoted Swan 71 survival. Nevertheless, G-CSF increased the expression levels of metalloproteinase-2 (MMP-2), vascular\nendothelial growth factor (VEGF) and integrin ?1, and also induced a migratory phenotype. On the other hand, we proved that G-CSF activated MAPKs ERK1/2 and p38, PI3K/Akt and NF-\n?B/I?B signaling pathways. By using specific pharmacological inhibitors and dominant negative mutants we verified that those pathways participated in some of the biological effects induced by G-CSF in Swan 71 cells. In addition, we observed that MAPK ERK1/2 and PI3K/Akt activated NF- ?B, and that PI3K acted as an upstream activator of MAPKs ERK1/2 and p38.\nThe whole results allowed us not only to elucidate the mechanism of action of G-CSF in trophoblastic cells, but also to reinforce the hypothesis that G-CSF, by promoting the acquisition of a migratory trophoblastic phenotype, would participate together with other factors of the maternal-fetal interface in the embryonic implantation and placenta development.